2021
DOI: 10.3390/geosciences11090383
|View full text |Cite
|
Sign up to set email alerts
|

Marine Monitoring for Offshore Geological Carbon Storage—A Review of Strategies, Technologies and Trends

Abstract: Carbon capture and storage (CCS) could significantly contribute to reducing greenhouse gas emissions and reaching international climate goals. In this process, CO2 is captured and injected into geological formations for permanent storage. The injected plume and its migration within the reservoir is carefully monitored, using geophysical methods. While it is considered unlikely that the injected CO2 should escape the reservoir and reach the marine environment, marine monitoring is required to verify that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Studies have shown that carbon capture and storage (CCS) can significantly help to reduce greenhouse gas emissions [1]. In many geoscience applications, CO 2 is captured and injected into geological formations for permanent storage [2].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that carbon capture and storage (CCS) can significantly help to reduce greenhouse gas emissions [1]. In many geoscience applications, CO 2 is captured and injected into geological formations for permanent storage [2].…”
Section: Introductionmentioning
confidence: 99%
“…The sensing mechanisms, performance, advantages and disadvantages of different detection methods and sensors, including point sensors and in situ sensors, are analyzed and compared. Compared to other reviews focusing on only one or several fields, such as seafood [32,33], nutrients [24,34] and carbon storage [35], this work provides a comprehensive description of commercial products and the latest development of the in situ marine sensors for different analytes. Some representative optical, chemical and biological marine sensors are summarized in the tables, and their characteristics are analyzed and compared in detail.…”
Section: Introductionmentioning
confidence: 99%